Antimicrobial activity of bacteriocin like inhibitory substance (BLIS) and lactic acid bacteria (LAB) isolated from traditional fermented buffalo milk from West Sumatra, Indonesia. Issue 1 (November 2021) - Hayati, F; Yuliana, T; Rialita, T
Abstract: Food preservation by chemical preservatives addition is not recommended in large quantities. However, lactic acid bacteria (LAB) metabolites can be used as a safe alternative. LAB can produce a type of antimicrobial peptide known as bacteriocin. One source of LAB that can be used as a bacteriocin-producing candidate is dadih, a traditional fermented buffalo milk product from West Sumatra, Indonesia. In this study, eight bacterial isolates isolated from dadih were identified using the catalase test and Gram straining and obtained 6 isolates that were taken as LAB. An antimicrobial activity test was carried out using the diffusion method on LAB liquid isolates suspension and crude bacteriocins from the six isolates. The isolates with the highest antimicrobial activity were DK8, the diameter of inhibiting zone of liquid isolates was 15.75 mm ( Salmonella sp. ), 14.25 mm ( Escherichia coli ), and 12.25 mm ( Staphylococcus aureus ). Meanwhile, the diameter of crude bacteriocin inhibition of DK 8 isolates was 8 mm ( Salmonella sp. ). 8 mm ( E. coli ), and 8.5 mm ( S. aureus ). Furthermore, 16S rRNA sequencing confirmed DK8 as Lactobacillus pentosus.